Correlation between mother's knowledge about fe tablets with the incidence of anemia in pregnant women at IMP Nursyamsiah, S.ST in 2022 - Rini Wahyuni; Siti Rohani (Universitas Aisyah Pringsewu, 2023)
The mother's understanding of FE tablets might have an impact on anemia. Pregnant women's knowledge should increase as a result of the counseling procedure. The research objective was to determine the correlation between the level of knowledge of pregnant women about FE tablets and the incidence of anemia in pregnant women at IMP Nursyamsiah S.ST. This research was conducted because there are still many pregnant women who experience anemia, which is as much as 33%. Cross-sectional quantitative research methodology was applied in this study. All 50 pregnant women in their third trimester at IMP Nursyamsiah S.ST in January 2022 comprised the study's population. Analysis of the data used the chi-square test. This study showed that the number of pregnant women with anemia in IMP was 16 pregnant women (32%), the number of pregnant women with a lack of knowledge was 16 pregnant women (32%). There is a significant correlation between the level of knowledge of pregnant women and the incidence of anemia at the Bakung Public Health Center in Teluk Betung District in 2021 with a P-Value = 0.000. As a suggestion, health workers can increase counseling for pregnant women and increase public understanding, especially for pregnant women, of the importance of Fe tablets in preventing anemia in pregnancy. Abstrak: Salah satu yang dapat mempengaruhi Anemia adalah pengetahuan ibu tentang tablet FE . Adanya proses penyuluhan diharapakan dapat meningkatkan pengetahuan ibu hamil. Tujuan penelitian ini adalah untuk mengetahui hubungan tingkat pengetahuan ibu hamil tentang tablet FE dengan kejadian anemia ibu hamil di PMB Nursyamsiah S.ST. Peneliatian ini dilakukan karena masih banyak ibu hamil mengalami Anemia yaitu sebanyak 33%. Desain yang digunakan dalam penelitian ini adalah kuantitatif dengan pendekatan cross sectional. Populasi dalam penelitian ini adalah seluruh ibu hamil trimester III di PMB Nursyamsiah S.ST pada bulan Januari tahun 2022 yang berjumlah 50 orang. Analisa data yang digunakan menggunakan uji chi square. Hasil penelitian ini didapatkan jumlah ibu hamil dengan anemia di PMB sebanyak 16 ibu hamil (32%), jumlah ibu hamil dengan tingkat pengetahuan kurang sebanyak 16 ibu hamil (32% ). Ada hubungan yang bermakna antara tingkat pengetahuan ibu hamil dengan kejadian anemia di Puskesmas Bakung Kecamatan Teluk Betung tahun 2021 dengan P-Value = 0,000 Meningkatkan penyuluhan kepada ibu hamil guna meningkatkan pemahaman masyarakat khususnya ibu hamil akan pentingnya tablet Fe dalam mencegah anemia pada kehamilan.